A Survey on Searching Approaches on Issues in Cloud Based Environment - Sahu, Priyanka Devi; Minj, Jasmine (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a concept of outsourcing the storage and processing capabilities for storing and managing data and computer programs. With the appearance of cloud computing, it has turned out to be progressively prominent for the owners of data to make available their information to public cloud servers at the time of permitting data users to retrieve this information. For some privacy reasons, a secure search on encrypted cloud information has boosted some of the research works in the single owner model. Normally with information measure capability and restricted battery life, looking on encrypted information imposes serious overhead to computing and communication also as a better power consumption for mobile device users that makes the encrypted search over mobile cloud terribly difficult. The aim of the paper is to conduct a survey on efficient searching techniques on data in cloud environments.